A bride for one night : Talmud tales - Calderon, Ruth, 1961- (University of Nebraska Press ; Jewish Publication Society, 2014)
Ruth Calderon has recently electrified the Jewish world with her teachings of talmudic texts. In this volume, her first to appear in English, she offers a fascinating window into some of the liveliest and most colorful stories in the Talmud. Calderon rewrites talmudic tales as richly imagined fictions, drawing us into the lives of such characters as the woman who risks her life for a sister suspected of adultery; a humble schoolteacher who rescues his village from drought; and a wife who dresses as a prostitute to seduce her pious husband in their garden. Breathing new life into an ancient.